OVERT THEFT AND THE PECULIARITIES OF THE QUALIFICATION - Abramavičius, Armanas; Vosyliūtė, Andželika (Teisė, 2017)
Article is devoted to analysis of Overt theft as aggravating theft, that is forseen in Paragraph 2 of Article 178 (theft) of The Criminal Code of the Republic of Lithuania. The conception of Overt theft under criminal law science and jurisprudence is given. The article reveals some peculiarities of incrimination and qualification of the aggravated theft.